Answer:
[tex](x + 3, y - 7)[/tex]
Step-by-step explanation:
Given
[tex]Function = (x,y)[/tex]
Translation:
[tex]Left = 3\ units[/tex]
[tex]Down = 7\ units[/tex]
Required
Determine the image of the function
Apply the first translation
[tex]Left = 3\ units[/tex]
When function (x,y) is 3 units translated left, we add the units to the x value.
The new function becomes:
[tex](x,y) -> (x + 3, y)[/tex]
Apply the second translation
[tex]Down = 7\ units[/tex]
We subtract 7 units from the y value
[tex](x,y) -> (x + 3, y)[/tex]
becomes:
[tex](x + 3, y) ->(x + 3, y - 7)[/tex]
Hence:
The image of the function is:
[tex](x + 3, y - 7)[/tex]